EKSTRAK ETANOL DAUN SAMBILOTO (ANDROGRAPHIS PANICULATA) MENURUNKAN HAI (HISTOLOGY ACTIVITY INDEKS)-KNODELL SCORE PADA HEPAR MENCIT (MUS MUSCULUS) JANTAN YANG DIINDUKSI CCL4 - Gede Gunawan Mahardika; Ni Wayan Sucindra Dewi; IGM. Aman (E-Jurnal Medika Udayana, 2020)
ABSTRACT Hepatitis is all types of inflammation in hepatocytes (liver cells), which caused by: infections (viruses, bacteria, and parasites), drugs, alcohol consumption, toxic substances and autoimmune diseases. Carbon tetrachloride can induce hepatitis. Sambiloto leaves (Andrographis paniculata) contains of flavonoids and andrographolide which have the potential as antioxidants. The aims of this study is to determine the hepatoprotective effect of Sambiloto leaves extract on mice liver that induced by tetrachloride carbon of toxic dose and evaluate using Knodell Score. The design of this study is a post-test only group control on 28 sample of male mice (Mus musculus) which divided into 4 groups; P1 given tetrachloride carbon (0.5,l/kgBB), P2 group was given Sambiloto leaves extract (50mg/kgBB/day), P3(100mg/kgBB/day) and P4 (200mg/kgBB/day). Extract was given during seven days and eight hour after last administration, all mice was given CCl4 toxic dose. On the eight day, the mice was terminated and examine the liver histopathological. Data analysed using One Way ANOVA and Post Hoc LSD. Significant score difference was found between the groups than only given tetrachloride carbon toxic dose and the group that given the extract. The optimal dose is 200mg/kgBB/day. There was an improvement effect of liver histopathology score by giving sambiloto leaves extract to mice that induced by tetrachloride carbon toxic dose. More advanced research is needed to determine the effective dose and toxic effects of giving sambiloto leaf extract. Keywords: Ethanol Extract of Sambiloto Leaf, HAI (Histology Activity Indeks)-Knodell Score, Hepatoprotectif, Mice (Mus musculus), Tetrachloride Carbon